Fluid biomarker and electrophysiological outcome measures for progressive MS trials. (October 2017) - Barro, Christian; Leocani, Letizia; Leppert, David; Comi, Giancarlo; Kappos, Ludwig; Kuhle, Jens
Progressive multiple sclerosis (MS) is characterized by insidious clinical worsening that is difficult to accurately quantify and predict. Biofluid markers and electrophysiological measures are potential candidate outcome measures in clinical trials, allowing the quantification of nervous damage occurring in the disease. Neurofilaments are highly specific neuronal proteins. They may have come closest to such applications by their higher concentrations repeatedly demonstrated in cerebrospinal fluid (CSF) in all stages of MS, during relapses, their responsiveness to disease-modifying treatments in relapsing and progressive MS and their associations with measures of inflammatory and degenerative magnetic resonance imaging (MRI) outcomes. Digital single-molecule array (Simoa) technology improves accuracy of bioassays in the quantification of neurofilament light chain (NfL) in serum and plasma. NfL seems to mark a common final path of neuroaxonal injury independent of specific causal pathways. CSF and blood levels of NfL are highly correlated across various diseases including MS, suggesting that blood measurements may be useful in assessing response to treatment and predicting future disease activity. Other biomarkers like matrix metalloproteinases, chemokines, or neurotrophic factors have not been studied to a similar extent. Such measures, especially in blood, need further validation to enter the trial arena or clinical practice. The broadening armamentarium of highly sensitive assay technologies in the future may shed even more light on patient heterogeneity and mechanisms leading to disability in MS. Evoked potentials (EPs) are used in clinical practice to measure central conduction of central sensorimotor pathways. They correlate with and predict the severity of clinical involvement of their corresponding function. Their validation for use in multicenter studies is still lacking, with the exception of visual EPs. If further validated, EPs and fluid biomarkers would represent useful outcome measures for clinical trials, being related to specific mechanisms of the ongoing pathologic changes.